Worldwide productivity in the hand and wrist literature: A bibliometric analysis of four highly cited subspecialty journals. (April 2016) - Mei, Xiaolong; Zhu, Xuwei; Zhang, Tao; Jia, Zhiwei; Wan, Chunyou
Abstract: Objective: Hand and wrist research has recently shown obvious progress. The quantity and quality of publications from different nations, however, have not been analyzed. In our study, we aimed to assess the characteristics of worldwide productivity in hand and wrist literature using highly cited subspecialty journals. Methods: Literature search using the Web of Science database was conducted to identify hand and wrist articles in four highly cited subspecialty journals from 2005 to 2014. The number of articles, impact factors and citations were analyzed to evaluate the contributions of different countries. Publication activity was adjusted for the countries by population size. Results: A total of 4268 publications were identified. The number of articles showed a significant increase of 2.10-fold between 2005 and 2014 (p = 0.0001). North America, West Europe, and East Asia were the most prolific areas. The majority of publications (92.03%) were from high-income countries, 7.97% from middle-income countries, and no publications from lower-income countries. The United States published the most articles (53.89%), followed by United Kingdom (6.51%), Japan (6.14%), Canada (3.70%), and China (3.37%). Articles originating from the United States showed the greatest number of total 5-year impact factors (5y-IF) (4059.56) and total citations (17, 998). When normalized to population size, United States ranked the first (7.16), followed by Sweden (6.53), and Netherlands (5.72). However, Netherlands (1.893) had the highest mean 5y-IF, followed by Germany (1.884) and Australia (1.883). Sweden had the highest average citations per article (11.38), followed by Germany (9.63), and Australia (9.08). Conclusions: The number of publications of hand and wrist research shows a significant increase during the past 10 years. The United States is the most productive country in hand and wrist literature. However, some European countries and Australia may have higher quality of articles according to mean 5y-IF and mean citations per article. Highlights: There is a significant increase in the hand and wrist research during the past 10 years. The majority of articles is published by high-income countries, whereas no paper from low-income countries. The United States is the most productive country in hand and wrist research. Some European countries and Australia may have higher quality of articles.